International Society of Sports Nutrition Position Stand: Long-Chain Omega-3 Polyunsaturated Fatty Acids - Ralf Jäger; Jeffery L. Heileson; Sidney Abou Sawan; Broderick L. Dickerson; Megan Leonard; Richard B. Kreider; Chad M. Kerksick; Stephen M. Cornish; Darren G. Candow; Dean M. Cordingley; Scott C. Forbes; Grant M. Tinsley; et al. (Journal of the International Society of Sports Nutrition)
Position Statement: The International Society of Sports Nutrition (ISSN) presents this position based on a critical examination of the literature surrounding the effects of long-chain omega-3 polyunsaturated fatty acid (ω-3 PUFA) supplementation on exercise performance, recovery, and brain health. This position stand is intended to provide a scientific foundation for athletes, dietitians, trainers, and other practitioners regarding the effects of supplemental ω-3 PUFA in healthy and athletic populations. The following conclusions represent the official position of the ISSN: Athletes may be at a higher risk for ω-3 PUFA insufficiency.Diets rich in ω-3 PUFA, including supplements, are effective strategies for increasing ω-3 PUFA levels.ω-3 PUFA supplementation, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), has been shown to enhance endurance capacity and cardiovascular function during aerobic-type exercise.ω-3 PUFA supplementation may not confer a muscle hypertrophic benefit in young adults.ω-3 PUFA supplementation in combination with resistance training may improve strength in a dose- and duration-dependent manner.ω-3 PUFA supplementation may decrease subjective measures of muscle soreness following intense exercise.ω-3 PUFA supplementation can positively affect various immune cell responses in athletic populations.Prophylactic ω-3 PUFA supplementation may offer neuroprotective benefits in athletes exposed to repeated head impacts.ω-3 PUFA supplementation is associated with improved sleep quality.ω-3 PUFA are classified as prebiotics; however, studies on the gut microbiome and gut health in athletes are currently lacking.